A Comprehensive Overview of the Current State of Development in Autonomous Vehicle Driving - Sun, Jingzhou (International Journal of Mechanical and Electrical Engineering, 2024)
The 21st century has witnessed a rapid evolution in information technology, leading to significant transformations in the automotive industry. The focus has shifted from purely mechanical enhancements to the advent of a new generation of vehicles equipped with intelligent driving technology. These smart vehicles are capable of perceiving their surroundings and adapting to real-time conditions and traffic, enabling assisted or even fully autonomous driving. This advancement promises substantial improvements in safety, environmental sustainability, and comfort, enhancing the overall driving experience. This paper provides a comprehensive overview of the current state of autonomous vehicle technology, focusing on the fundamental principles of intelligent driving. It delves into three key areas: environmental perception, path planning, and the application of artificial intelligence in autonomous driving systems.